2017
DOI: 10.1002/jcph.908
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology Tools and Evaluations to Facilitate Comprehensive Dose Finding in Oncology: A Continuous Risk‐Benefit Approach

Abstract: Targeted therapies are now considered an integral component in the treatment armamentarium for many malignancies, and the approach to developing these drugs needs to be refined from the previous cytotoxic paradigm of toxicity-guided dose finding and identification of maximum tolerated dose to a paradigm driven by target activity. Moving away from the toxicity-driven dose finding and justification model requires an integrated approach in order to adequately characterize the risk-benefit of a drug. This approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Evaluation of the effects of intrinsic (e.g., functional capacity of eliminating organs) and extrinsic (e.g., drug-drug interactions) factors on PK is a crucial component of the clinical pharmacology characterization of anticancer agents to inform appropriate dosing and administration across patient populations and clinical contexts of use [18,19]. Radiolabeled mass balance studies play an important role in quantitatively defining routes of elimination and clearance mechanisms, thereby providing valuable inputs to inform a scientifically guided and rational approach to evaluating intrinsic/extrinsic factor effects on PK [20].This study evaluated the mass balance, PK, routes of elimination, and safety of the NAE inhibitor pevonedistat in 8 patients with advanced solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the effects of intrinsic (e.g., functional capacity of eliminating organs) and extrinsic (e.g., drug-drug interactions) factors on PK is a crucial component of the clinical pharmacology characterization of anticancer agents to inform appropriate dosing and administration across patient populations and clinical contexts of use [18,19]. Radiolabeled mass balance studies play an important role in quantitatively defining routes of elimination and clearance mechanisms, thereby providing valuable inputs to inform a scientifically guided and rational approach to evaluating intrinsic/extrinsic factor effects on PK [20].This study evaluated the mass balance, PK, routes of elimination, and safety of the NAE inhibitor pevonedistat in 8 patients with advanced solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of highly active and innovative therapies in areas of high unmet medical need, dose and regimen optimization may not be complete prior to initial approval, especially in the context of accelerated regulatory approvals and adaptive licensing pathways. For example, recent reviews have identified several examples of ongoing postmarketing optimization of the initial approved doses of anticancer drugs . In this context, exposure/dose‐response MBMA models can be valuable in identifying the determinants of therapeutic index of approved drugs (e.g., optimal dose/schedule, risk factors for adverse events of clinical importance).…”
Section: Mbma Applications In Comparative Effectiveness Research and mentioning
confidence: 99%
“…For example, recent reviews have identified several examples of ongoing postmarketing optimization of the initial approved doses of anticancer drugs. [53][54][55] In this context, exposure/doseresponse MBMA models can be valuable in identifying the determinants of therapeutic index of approved drugs (e.g., optimal dose/ schedule, risk factors for adverse events of clinical importance). Such findings can result in hypotheses for enhancing postapproval dose optimization efforts and risk management guidance.…”
Section: Mbma Applications In Comparative Effectiveness Research and mentioning
confidence: 99%
“…Either way, patient safety must be ensured without choking innovation. Finally, further clinical pharmacology expertise is required (1) in drug development to influence the major decision makers, and (2) in clinical practice to train clinicians about MIPD and to determine a framework of quality control at the point of care.…”
Section: Overcoming Barriersmentioning
confidence: 99%